Biotechnological tools for genetic improvement of Trichoderma - Liliana Villao-Uzho; Fernando Espinoza-Lozano; Luis Galarza-Romero; Efrén Santos-Ordóñez (Scientia Agropecuaria)
Trichoderma is a cosmopolitan fungus widely distributed around the world. The different uses of this beneficial fungus are varied in several industries, like agriculture, textile, and paper, including the pharmaceutical industry. The genus Trichoderma has other mechanisms of action, including the production of different enzymes and secreted secondary metabolites used in various industries. The genomes of different Trichoderma species have been sequenced to identify the mechanisms for producing several compounds. The advancement of multiple technologies has allowed the development of transformation tools for the genetic improvement of Trichoderma, thus increasing biomass, primary and secondary metabolites, and enzymes. Therefore, genetic modification aims to increase compound production in several Trichoderma strains. Characterization of Trichoderma through gene expression analysis is essential for biotechnology applications. It helps counteract one of the most challenging problems for agriculture today, including climate change and the appearance of pathogens that attack crops with high commercial and food demand. In conclusion, this review analyzes various strategies to improve Trichoderma strains genetically and their multiple applications in the agricultural, textile, paper, and pharmaceutical industries. As a recommendation for future studies with potential impact, the optimization of specific genetic modifications in Trichoderma strains is recommended to improve their adaptability and effectiveness in combating emerging challenges in agriculture, especially those linked to climate change. Investigating possible synergies between genetically modified Trichoderma strains and environmentally sustainable agricultural practices could contribute to developing solutions for crop protection and yield improvement.